Explanatory factors of polydrug use in mid-late teens and the relevance of information sources: Correlational and configurational assessment in Tarragona (Spain) - Jorge de Andrés-Sánchez; Francesc Valls-Fonayet; Anna Sánchez-Aragón; Anna Sánchez-Aragón; Inma Pastor-Gosálbez; Angel Belzunegui-Eraso (AIMS Press, 2024)
Background Substance use among adolescents is a public health problem, and the simultaneous use of multiple substances aggravates this problem. Although the facilitators of specific substance use in adolescents have been widely investigated, polydrug use is a less common topic. Likewise, the role that the origin of the information available to adolescents regarding substance use plays in relation to polydrug use is practically unexplored. Objectives This work analyzed the relevance of the origin of the information sources available to adolescents regarding substance use, among which we distinguished those that were monitored (or supervised) by public agencies from those that were unmonitored (or unsupervised) in the consumption of more than one substance. As control variables, we considered three individual factors and four environmental factors. The relevance of these sources was analysed from a dual perspective: on the one hand, their statistical relevance was measured, and on the other hand, how they combined with the control variables was analysed to identify risk and risk-free profiles in substance poly-drug use. Methods This paper utilized a sample of N = 573 adolescents aged ≥17 years. This sample was collected from a survey administered in the spring of 2023. We examined the impact of unmonitored information sources (peers, siblings, and the Internet) and supervised sources (school, parents, and media) on the combined consumption of alcohol, tobacco, and cannabis. Additionally, we took three individual factors (gender, early onset of alcohol, and tobacco use) and four environmental factors (parental control, alcohol, tobacco, and cannabis use among peers) into account as control variables. Initially, we conducted a regression analysis to adjust for the impact of these factors on polydrug use. Subsequently, we employed a fuzzy set qualitative analysis (fsQCA) to investigate how predictor factors combined with the formation of adolescent profiles associated with polydrug consumption and nonconsumption. Results Unmonitored information sources were associated with a greater incidence of poly consumption, with ORs of 1.703 and p values of 0.004. However, the protective effects of regulated information sources remained ambiguous. Among the variables positively linked with of polydrug use, are female sex (OR = 1.329, p = 0.0076), early alcohol consumption (OR = 4.680, p < 0.0001), and early tobacco consumption (OR = 3.242, p < 0.001) were the most important. Peer drinking (OR = 1.556, p = 0.0187) and peer cannabis use (OR = 1.351, p = 0.0226) were also significantly correlated. The use of the fsQCA made it possible to identify the profiles of adolescents associated to polysubstance use and non-use. The conditions of the configurations that explained use were characterized by an early onset of the joint consumption of tobacco and alcohol. The profile of non-consuming adolescents is that of adolescents whose peers do not use tobacco or cannabis and who have parental control and monitored sources.